2015
DOI: 10.1021/es505928w
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Mercury in Forests along a Montane Elevation Gradient

Abstract: Atmospheric mercury (Hg) deposition varies along elevation gradients and is influenced by both orographic and biological factors. We quantified total Hg deposition over a 2 year period at 24 forest sites at Whiteface Mountain, NY, USA, that ranged from 450 to 1450 m above sea level and covered three distinct forest types: deciduous/hardwood forest (14.1 μg/m2-yr), spruce/fir forest (33.8 μg/m2-yr), and stunted growth alpine/fir forest (44.0 μg/m2-yr). Atmospheric Hg deposition increased with elevation, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 48 publications
10
67
1
1
Order By: Relevance
“…Although all our litter depth profiles are located in coniferous forests, similar enrichments of Hg concentrations in older litter has been observed in both coniferous and deciduous forests [ Hall and St . Louis , ; Demers et al ., ; Obrist et al ., , ; Blackwell et al ., ; Blackwell and Driscoll , ].…”
Section: Resultsmentioning
confidence: 99%
“…Although all our litter depth profiles are located in coniferous forests, similar enrichments of Hg concentrations in older litter has been observed in both coniferous and deciduous forests [ Hall and St . Louis , ; Demers et al ., ; Obrist et al ., , ; Blackwell et al ., ; Blackwell and Driscoll , ].…”
Section: Resultsmentioning
confidence: 99%
“…At Whiteface, the summit has been estimated to be covered by clouds for 40–45% of the year, with significant cloud coverage also found in the coniferous zone [ Mohnen , ]. Consequently, previous studies have found cloudwater contribution to THg deposition at Whiteface to be the most important input of Hg to the alpine zone and a comparable input to throughfall Hg deposition in the coniferous zone [ Blackwell and Driscoll , ]. We also find cloudwater to be an important contributor in alpine and coniferous zones.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, conifers are more efficient at filtering atmospheric Hg particles than deciduous trees due to greater surface roughness, high leaf area index, and a canopy structure that decreases air flow and thereby enhances particle adsorption [ Kolka et al, ; Rea et al, ; Johnson et al, ; Witt et al, ]. As a result, THg inputs via throughfall are typically the predominant source of THg to coniferous forests [ Demers et al, ], which is consistent with our results and previous work at Whiteface [ Blackwell and Driscoll , ]. Throughfall inputs of THg to alpine zones, however, are reduced due to lower total leaf area associated with sparse tree density and lower canopy height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have suggested that plants are a net sink for atmospheric Hg through leaf assimilation (Millhollen et al, 2006a;Stamenkovic and Gustin, 2009;Rutter et al, 2011b;Cui et al, 2014). Using Hg concentrations in plant tissues and net primary productivity as a proxy for atmospheric Hg deposition, Obrist (2007) (Blackwell and Driscoll, 2015a, b;Obrist et al, 2011); and ∼ 90 % boreal forest soil Hg was believed to be originated from litterfall input (Jiskra et al, 2015). These studies suggest that the forest ecosystem is likely a large atmospheric Hg sink, although these bulk proxy methods are not sufficiently sophisticated to resolve the global Hg mass balances.…”
Section: Fluxes Over Vegetated Surfaces Likely a Sink But Large Uncermentioning
confidence: 99%